Hubungan Shalat Tahajud dengan Kecerdasan Emosional pada Mahasiswa - Muzhdhalifatul Azizah; Kartika Aulia Rahmi; Jeni Fadhila; Amalia Kartika Yani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Students tend to face demands in their coursework so that changes arise in various individual functional aspects such as physical, psychological and social. This change requires students to be able to adapt, this condition requires students to have high emotional intelligence because it is directly related to everyday life, especially to managing negative emotions. If you have good emotional intelligence, you can have an impact on creating enjoyment in learning, getting rid of things that can disturb and hinder the learning process. One way to increase emotional intelligence is by performing the tahajjud prayer. The lesson of the Tahajjud prayer is maintaining individual psychological health, such as the heart's potential for emotions, the mind for thinking. The aim of this research is to see whether there is a relationship between the Tahajjud prayer and emotional intelligence in students. This research used a quantitative approach with a questionnaire method with 100 students as subjects. The results of this research are that there is a positive relationship between midnight prayer and emotional intelligence. It is hoped that future researchers will use a qualitative approach to find out how the tahajjud prayer benefits a person's emotional intelligence.